Comprehensive evaluation of an advanced street canyon air pollution model. (1st February 2021) - Hood, Christina; Stocker, Jenny; Seaton, Martin; Johnson, Kate; O'Neill, James; Thorne, Lewis; Carruthers, David
ABSTRACT: A street canyon pollution dispersion model is described which accounts for a wide range of canyon geometries including deep and/or asymmetric canyons. The model uses up to six component sources to represent different effects of street canyons on the dispersion of road traffic emissions. The final concentration is a weighted sum of the component concentrations dependent on output point location; canyon geometry; and wind direction relative to canyon orientation. Conventional approaches to modeling pollution in street canyons, such as the "Operational Street Pollution Model" (OSPM), do not account for canyons with high aspect ratios, pavements, and building porosity, so are not applicable for all urban morphologies. The new model has been implemented within the widely used, street-level resolution ADMS-Urban air quality model, which is used for air quality assessment and forecasting in cities such as Hong Kong where high-rise buildings form deep and complex street canyons. The new model is evaluated in relation to measured pollutant concentration data from the "Optimisation of modelling methods for traffic pollution in streets" (TRAPOS) project and routine measurements from 42 monitoring sites in London. Comparisons have been made between modeling using the new canyon model; a simpler approach to canyon modeling based on the OSPM formulation; and without any inclusion of canyon effects. The TRAPOS dataset has been used to highlight the model's ability to replicate the dependence of concentration on wind speed and direction, and also to show improved model performance for the prediction of high concentration values, which is particularly important for model applications such as planning and assessment. The London dataset, in which the street canyons are less well defined, has also been used to demonstrate improved model performance for this advanced approach compared to the simpler methods, by categorizing the measurement locations according to site type (background, near-road, and strong canyon). Implications : Currently available air dispersion models do not allow for a number of geometric features that influence air dispersion within street canyon environments. The new advanced street canyon model described in this paper accounts for: emissions from each road carriageway separately; canyon asymmetry; canyon porosity; and pavements. The extensive model evaluation presented shows that the new model demonstrates good performance, better than more basic approaches in which the complex geometries that define "canyons" are neglected.